Precise Cerebral Vascular Atlas in Stereotaxic Coordinates of Whole Mouse Brain - Xiong, Benyi; Li, Anan; Lou, Yang; Chen, Shangbin; Long, Ben; Peng, Jie; Yang, Zhongqin; Xu, Tonghui; Yang, Xiaoquan; Li, Xiangning; Jiang, Tao; Luo, Qingming; et al. (Frontiers in Neuroanatomy, 2017)
Understanding amazingly complex brain functions and pathologies requires a complete cerebral vascular atlas in stereotaxic coordinates. Making a precise atlas for cerebral arteries and veins has been a century-old objective in neuroscience and neuropathology. Using micro-optical sectioning tomography (MOST) with a modified Nissl staining method, we acquired five mouse brain data sets containing arteries, veins and microvessels. Based on the brain-wide vascular spatial structures and brain regions indicated by cytoarchitecture in one and the same mouse brain, we reconstructed and annotated the vascular system atlas of both arteries and veins of the whole mouse brain for the first time. The distributing patterns of the vascular system within the brain regions were acquired and our results show that the patterns of individual vessels are different from each other. Reconstruction and statistical analysis of the microvascular network, including derivation of quantitative vascular densities, indicate significant differences mainly in vessels with diameters less than 8 μm and large than 20 μm across different brain regions. Our precise cerebral vascular atlas provides an important resource and approach for quantitative studies of brain functions and diseases